2018
DOI: 10.1016/j.redox.2018.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Curcumol induces RIPK1/RIPK3 complex-dependent necroptosis via JNK1/2-ROS signaling in hepatic stellate cells

Abstract: It is generally recognized that hepatic fibrogenesis is an end result of increased extracellular matrix (ECM) production from the activation and proliferation of hepatic stellate cells (HSCs). An in-depth understanding of the mechanisms of HSC necroptosis might provide a new therapeutic strategy for prevention and treatment of hepatic fibrosis. In this study, we attempted to investigate the effect of curcumol on necroptosis in HSCs, and further to explore the molecular mechanisms. We found that curcumol amelio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 60 publications
4
88
0
Order By: Relevance
“…Therefore, effective suppression of inflammation and improvement of inflammatory microenvironment are critical to control the progression of liver fibrosis. Currently, anti‐inflammatory drugs have been widely used to control liver inflammation in clinical, of which, remarkable achievements has been made using natural products to prevention and treatment of liver fibrosis in experimental and clinical research . Tripterygium wilfordii Hook F (TwHF), a Chinese medicinal plant, shows potent anti‐inflammatory effect, especially in rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, effective suppression of inflammation and improvement of inflammatory microenvironment are critical to control the progression of liver fibrosis. Currently, anti‐inflammatory drugs have been widely used to control liver inflammation in clinical, of which, remarkable achievements has been made using natural products to prevention and treatment of liver fibrosis in experimental and clinical research . Tripterygium wilfordii Hook F (TwHF), a Chinese medicinal plant, shows potent anti‐inflammatory effect, especially in rheumatoid arthritis (RA).…”
Section: Discussionmentioning
confidence: 99%
“…The active ingredients extracted from Traditional Chinese Medicine have become important choices for the treatment of several chronic diseases, including liver fibrosis . Celastrol is a pentacyclic triterpenoid compound (the chemical structure of celastrol is shown in Figure ), which is isolated from a common clinical used Traditional Chinese Medicine named Tripterygium wilfordii Hook F. Celastrol possesses multiple pharmacological effects and showed potent anti‐inflammatory effect against many disease models, and however, few reports can be seen regarding the anti‐inflammatory potential of celastrol in liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also explained that different active components in natural medicinal plants could alleviate liver fibrosis by inhibiting pathological angiogenesis . We previously reported that curcumol mitigated liver pathological changes via promoting activated HSC necroptosis . However, the effects of curcumol on LSEC angiogenesis in liver fibrosis had not been investigated, and the underlying mechanism remained to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Sixty mice were randomly divided into six groups (n = 10), named separately control, CCl 4 , CCl 4 + vector, CCl 4 + Smo, CCl 4 + curcumol and CCl 4 + Smo+curcumol. The mice in the drug intervention groups were intraperitoneal injected with curcumol (Shanghai Institute of Material Medical) suspension (dissolved in oil at 5 mg/mL) at 30 mg/kg . All animals got 24 hours fasting at the end of the experiment and then executed to take blood and liver.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation